Comparative Evaluation of the ETDRS Visual Acuity Chart and Arclight Cloth Chart (ARCchart) for Primary Eye Care in Resource-Limited Settings - Jaffray, Christine; Strang, Niall; Kousha, Obaid; Galloway, Gavin; Sweeney, Laura; Blaikie, Andrew (Scandinavian Journal of Optometry and Visual Science, 2023)
This study compared the Arclight Cloth Chart (ARCchart) to the gold standard ETDRS chart for visual acuity (VA) measurement in 63 participants. Despite its potential limitations as a tool to measure subtle changes in VA over time, the ARCchart showed a limit of agreement between -0.23logMAR and 0.26logMAR with ETDRS values. It demonstrated 93% (95% Confidence Interval 86% to 100%) sensitivity and 90% (84% to 97%) specificity when used to screen for vision worse than 0.20logMAR. This low-cost, portable cloth VA chart is a valuable alternative for measuring VA and screening for low vision in resource poor settings.